"Physics is supposed to be spoken of with a bit of irony": unknown speech by L D Landau, 8 April 1960. (January 2018) - Druzhinin, P A
Abstract: A previously unknown speech by Lev Landau dated 8 April 1960 has been published, as transcribed from a unique tape recording obtained from the Russian State Phonogram Archive (Moscow). This is Landau's only true public speech known to have been recorded.